Islamic Knowledge Management Reservoir Adaptation to Information and Digitalize Technology for Global Islamic Higher Education Institution - Othman, Khatijah; Yaakub, Muhamadul Bakir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Abstract. In a digitalized environment, Islamic Higher Education Institutions (IHEI) must organize knowledge effectively to uphold their fundamental values and principles. The concept of IKM is a primary concern for IHEIs, particularly among administrators, scholars, and educators. Within the scope of this study, IKM is regarded as an essential strategic approach for knowledge development in IHEIs. This perspective arises not only from its systematic differentiation, criteria, and functions but also from its ability to enhance knowledge responsibility, legitimacy, truth, and sustainability. In the context of the digital era, given that knowledge is a critical resource for IHEIs, it is crucial to understand how digital innovation can add value to sustaining IKM. A robust IHEI should institutionalize continuous learning and sharing protocols, leveraging digitalization, IoT, and big data systems as the core engines of its strategy, which is firmly rooted in the primary knowledge of the Quran and Hadith. IKM acknowledges the transformative impact of digital innovation on IHEIs, improving efficiency and the quality of knowledge by combining human and technological resources to generate sustainable value. A centralized digital reservoir of Islamic knowledge from around the world can help establish organizational knowledge as an asset. This approach can optimize organizational performance and drive growth by harnessing excellent human resources, fostering a healthy organizational structure and culture, deploying smart IT infrastructure, ensuring big data digital storage, and utilizing advanced artificial intelligence systems effectively.